SWEARING AND ITS MOTIVES IN THE ANTOLOGI RASA NOVEL - Prawinanto, Adityo; Prasetyo, Hardi; Bram, Barli (English Department of Faculty of Tarbiyah and Teacher Training, 2020)
This paper investigated English swear words used in a novel. This study was urgent to conduct because using swear words is a natural behavior in communication which is indicated by the employment of certain swear words to express emotion, to reduce frustrated feeling, and to show solidarity to others. Two research points to resolve were as follows: what types of swearing which the main character used and what motives for swearing in the novel. Data, consisting of 46 swear words, were collected from the Antologi Rasa novel written by Ika Natassa, and were investigated using a content analysis. Findings showed the following: 26 (56.5%) occurrences of auxiliary swearing, 12 (26.1%) of expletives swearing, 4 (8.7%) of abusive swearing, and 4 (8.7 %) of humorous swearing. Three motives for the main character to swear were as follows: psychological motives (23 occurrences or 50.0 %), social motives (19 or 41.30%), and linguistic motives (4 or 8.70%).